The Impact of Stock Prices on Consumption Growth through the Confidence Channel: A Cointegratioin Analysis of the United States - Nguyen, Kim (Université d'Ottawa | University of Ottawa, 2012)
The paper provides an empirical analysis of the effect of stock prices on consumer expenditure through the confidence channel in the United States. Changes in stock prices may affect consumption in two ways: the wealth effect and the confidence effect. Th